For Early Childhood at Playgroup Darunnajah in the Development of English Skills through Media - Widiani, Luh; Athar, Lalu Mohamad Iswadi (ARZUSIN, 2022)
The implementation of this Community Service aims to train the English language skills of students at the Playgroup Anak Soleh Darunnajah. The media used in this community service activity is song related to English vocabulary material. The participants of this community service are students at the Playgroup Anak Soleh Darunnajah Duman Lingsar. The result of this community service is an increase in English language skills and learning that is easier to understand and fun for students at the Playgroup Anak Soleh Darunnajah.